Exhaust emission of single cylinder diesel engine by using tire disposal fuel - Mohd Herzwan, Hamzah (2010)
This report deals with the emission of a single cylinder diesel engine and also the fuel consumption. The objectives of this report are to study the emission characteristics and the fuel consumption of a single cylinder diesel engine that are using tire scrap fuel compared to diesel fuel. This report describes the experimental setups and procedures for analyzing the emission characteristics and also the fuel consumption due to usage of the both fuels with the diesel engine running with no load exerted on it. The engine speed is variable. Detail studies about the experimental setup and components have been done before the experiment started. Data that are required for the analysis is obtained from the experiments. The fuel consumption is analyzed using the fuel flow meter and results for both fuel usages are compared in graph. The exhaust gas emission such as NO, NOx, CO, CO2, and O2 is analyzed using the exhaust gas analyzer and the results for both fuel usages are plotted in graph and compared. Calculations and analysis have been done after all the required data needed for the report is obtained. The results from the experiment show that the diesel fuel is better than tire scrap fuel in term of fuel consumption, CO emissions and CO2 emissions and vice versa for the other parameters.